THE EFFECT OF PROCUREMENT CONVENTION ON FOODS AND BEVERAGES INCOME IN SANUR PARADISE PLAZA HOTEL - Nesia Agnatasia; Francisca Titing Koerniawaty (Institut Pariwisata dan Bisnis Internasional, 2015)
This study is genenerally aimed at determining the effect of conventions’ activities to the income of food and beverage at the Sanur Paradise Plaza Hotel and specifically determining the types of convention and determining percentation of food and beverage income toward the conventions’ activities at the Sanur Paradise Plaza Hotel The data were collected through qualitative and qualitative method with the use of interview and documentation. This research found that there is a significant effect on the total supply of conventions to the income of food and beverage at the Sanur Paradise Plaza Hotel. It can be seen from the result of data analysis by using the simple of linear regression that show the coefficient of correlation R= 0.947 in which it indicates the existence of a positive relationship among procurement and very strong convention on food and beverage revenue. Meanwhile, the coefficient of determination is 89.6% that indicates that the provision of the convention have a direct and significant effect on the income of food and beverages.